Problem drinking, wellbeing and mortality risk in Chinese men: findings from the China Kadoorie Biobank. (6th January 2020) - Im, Pek Kei; Millwood, Iona Y.; Chen, Yiping; Guo, Yu; Du, Huaidong; Kartsonaki, Christiana; Bian, Zheng; Tan, Yunlong; Su, Jian; Li, Yilei; Yu, Canqing; Lv, Jun; et al.
Abstract: Aims: To assess the associations of problem drinking with wellbeing and mortality in Chinese men. Design: Population‐based prospective cohort study. Setting: Ten diverse areas across China. Participants: A total of 210 259 men aged 30–79 years enrolled into China Kadoorie Biobank between 2004 and 2008. Measurements: Self‐reported alcohol intake and indicators of problem drinking (i.e. drinking in the morning, unable to stop drinking, unable to work due to drinking, negative emotions after drinking, having shakes after stopping drinking) were assessed by questionnaire at baseline, along with stressful life events (e.g. divorce, income loss, violence) and wellbeing‐related measures (e.g. life satisfaction, sleep problems, depression, anxiety). Problem drinking was defined as reporting at least one of the drinking problem indicators. Follow‐up for mortality and hospitalized events was through linkage to death registries and national health insurance systems. Multivariate logistic regression models assessed cross‐sectional relationships between problem drinking and stressful life events/wellbeing. Cox proportional hazards regression models estimated prospective associations of problem drinking with mortality/hospitalized events. Findings: A third of men were current regular drinkers (i.e. drank alcohol at least weekly), 24% of whom reported problem drinking: 8% of all men. Experience of stressful life events in the past 2 years, especially income loss [odds ratio (OR) = 1.86, 95% confidence interval (CI) = 1.45–2.39], was associated with increased problem drinking. Compared with low‐risk drinkers (i.e. intake < 200 g/week, no reported problem drinking or habitual heavy drinking episodes), men with problem drinking had poorer self‐reported health, poorer life satisfaction and sleep problems, and were more likely to have symptoms of depression and anxiety. Men with two or more problem drinking indicators had an approximately twofold higher risk for all‐cause mortality as well as mortality and morbidity from external causes (i.e. injuries), respectively, and 15% higher risk for any hospitalization, compared with low‐risk drinkers (all P  < 0.01). Conclusion: Eight per cent of men in China are problem drinkers, and this is associated with significantly increased risk of physical and mental health problems and premature death.